Development and validation of a nomogram for predicting the clearance of jaundice in children with biliary Atresia after Kasai portoenterostomy - Lu, Zhengchen; Ding, Zequan; Zhang, Ruyi; Zhu, Zhongxian; Li, Wei; Xie, Hua; Tang, Weibing (Langenbeck's archives of surgery, 2025)
Purpose Kasai portoenterostomy (KPE) is a major treatment option for biliary atresia (BA). A rapid and early clearance of jaundice (CJ) following KPE is essential for a good long-term prognosis of BA. The present study aims to use the perioperative tests to create a nomogram for predicting early CJ in children with BA after KPE. Methods A total of 123 children with BA were randomized into a training cohort ( n = 87) and a testing cohort ( n = 36). Based on the value of total bilirubin (TB) at 3 months after KPE, subjects were divided into CJ group and unsuccessful clearance of jaundice (UCJ) group. Stepwise univariate and multivariate analyses were performed to identify risk factors of CJ, and a nomogram was created to predict CJ at 3 months after KPE in children with BA through the multivariate logistic regression analysis. Internal validation and calibration of the nomogram were conducted in both the training and testing cohorts. Results Age at KPE, postoperative aspartate transaminase (AST) level at two weeks, change ratio (CR) of direct bilirubin (DB) at two weeks post-KPE and fibrosis score (F-score) at KPE were independent risk factors of CJ at 3 months after KPE in children with BA. A nomogram to predict CJ at 3 months after KPE in children with BA was plotted involving the above four risk factors, achieving area under curves (AUC) of 0.861 and 0.885 in the training cohort and validation cohort, respectively. The calibration curve and decision curve analysis (DCA) validated the acceptable diagnostic performance of the nomogram in discriminating CJ at 3 months after KPE in children with BA of both cohorts. Conclusion This study developed and validated a nomogram incorporating four indictors, including Age at KPE, postoperative AST level at two weeks, CR of DB at two weeks post-KPE and F-score at KPE, may be useful for predicting CJ at 3 months after KPE in children with BA.